Genetic diversity and structure of Bipolaris oryzae and Exserohilum rostratum populations causing brown spot of rice in Burkina Faso based on genotyping-by-sequencing - Kaboré, Kouka Hilaire; Kassankogno, Abalo Itolou; Adreit, Henri; Milazzo, Joëlle; Guillou, Sonia; Blondin, Laurence; Chopin, Laurie; Ravel, Sébastien; Charriat, Florian; Barro, Mariam; Tollenaere, Charlottte; Lebrun, Marc-Henri; et al. (Frontiers in Plant Science, 2022)
In recent years, Brown spot disease of rice (BSR) has been observed on leaves and seeds of rice in all rice-growing areas of Burkina Faso. Bipolaris oryzae and Exserohilum rostratum are the main fungal species isolated from BSR infected tissues and they are frequently observed in the same field. However, we are lacking information on the genetic diversity and population structure of these fungi in Burkina Faso. The mode of reproduction also unknown. The genetic diversity of isolates of B. oryzae (n=61) and E. rostratum (n=151) collected from major rice-growing areas of Burkina Faso, was estimated using genotyping-by-sequencing (GBS). The mean values for nucleotide diversity (π) were 1.9 x10-4 for B. oryzae and 4.8 x10-4 for E. rostratum. There is no genetic differentiation between the geographical populations of each species. The analysis of molecular variance revealed that 89% and 94% of the genetic variances were within the populations of B. oryzae and E. rostratum, respectively. For both species, four genetic clusters were identified by two clustering methods (DAPC and sNMF). The distribution of these genetic groups was independent of the geographical origin of the isolates. Evidence of recombination was detected in the populations of B. oryzae and E. rostratum. For B. oryzae balanced mating type ratios were supporting sexual reproduction. For E. rostratum over representation of MAT1-2 isolates (79%) suggested a predominant asexual reproduction. This study provides important information on the biology and genetics of B. oryzae and E. rostratum in Burkina Faso.